2010
DOI: 10.1007/s12603-010-0022-0
|View full text |Cite
|
Sign up to set email alerts
|

The primary care physician and Alzheimer's disease: An international position paper

Abstract: This paper aims to define the role of the primary care physician (PCP) in the management of Alzheimer's disease (AD) and to propose a model for a work plan. The proposals in this position paper stem from a collaborative work of experts involved in the care of AD patients. It combines evidence from a literature review and expert's opinions who met in Paris, France, on July 2009 during the International Association of Geriatrics and Gerontology (IAGG) World Congress. The PCP's intervention appears essential at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 86 publications
1
55
0
5
Order By: Relevance
“…29 Primary care services are the first point of contact and main healthcare service for people with dementia. [30][31][32] It has been shown that the quality of annual reviews done in primary care for dementia is suboptimal and, despite a high prevalence of vascular diseases, over one-quarter of individuals diagnosed with dementia are prescribed antipsychotic medications that are known to increase the risk of cerebrovascular accidents and mortality. 33 In the current study, the quality of care for vascular conditions and risk factors received by…”
Section: Introductionmentioning
confidence: 99%
“…29 Primary care services are the first point of contact and main healthcare service for people with dementia. [30][31][32] It has been shown that the quality of annual reviews done in primary care for dementia is suboptimal and, despite a high prevalence of vascular diseases, over one-quarter of individuals diagnosed with dementia are prescribed antipsychotic medications that are known to increase the risk of cerebrovascular accidents and mortality. 33 In the current study, the quality of care for vascular conditions and risk factors received by…”
Section: Introductionmentioning
confidence: 99%
“…8 Primary care services are the first point of contact and main healthcare service for people with dementia. [9][10][11] In 2006, the annual dementia review was first introduced as a quality indicator to the UK Quality and Outcomes Framework (QOF) pay-for-performance guidelines for general practice. 12 This review, along with an indicator relating to a register of all people diagnosed with dementia in each practice, requires that there is a record of an annual dementia review from the previous 15 months for all patients on the dementia register.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons careful thought ought to be given to the development of more efficient and innovative care provision and pathways that will be able to amalgamate all three strategies, to a lesser or greater degree. Only in this way will primary care practitioners be able to achieve high standards of care for their patients with dementia (29).…”
Section: Resultsmentioning
confidence: 99%